(untitled) (Indian Forester, 1932)
West Australian sandalwood oil is obtained from a species which is named by the kew authorities as Eucarya spicata, R. Br. "Commerical" West Australian oil is a mixture of the oils of Eucaria spicata and Santalum lanceolatum.